2015
DOI: 10.1186/s12933-015-0296-y
|View full text |Cite
|
Sign up to set email alerts
|

Patients with coronary artery disease and diabetes need improved management: a report from the EUROASPIRE IV survey: a registry from the EuroObservational Research Programme of the European Society of Cardiology

Abstract: BackgroundIn order to influence every day clinical practice professional organisations issue management guidelines. Cross-sectional surveys are used to evaluate the implementation of such guidelines. The present survey investigated screening for glucose perturbations in people with coronary artery disease and compared patients with known and newly detected type 2 diabetes with those without diabetes in terms of their life-style and pharmacological risk factor management in relation to contemporary European gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 35 publications
6
63
0
5
Order By: Relevance
“…По дан-ным исследования NATION, наиболее высокая частота развития СД2 отмечалась у людей в возрасте 65-69 лет, что соответствует недавно представленным в США дан-ным, где распространенность СД2 среди людей ≥65 лет составляет 24,7% [11]. Полученные сведения важны, так как в этой возрастной группе наблюдается высокая распространенность заболеваний сердечно-сосудистой системы, терапия которых становится более сложной при наличии сопутствующего СД [12,13]. Хотя распростра-ненность СД2 увеличивалась с возрастом, у людей в воз-расте ≥70 лет такой тенденции не отмечено.…”
Section: Discussionunclassified
“…По дан-ным исследования NATION, наиболее высокая частота развития СД2 отмечалась у людей в возрасте 65-69 лет, что соответствует недавно представленным в США дан-ным, где распространенность СД2 среди людей ≥65 лет составляет 24,7% [11]. Полученные сведения важны, так как в этой возрастной группе наблюдается высокая распространенность заболеваний сердечно-сосудистой системы, терапия которых становится более сложной при наличии сопутствующего СД [12,13]. Хотя распростра-ненность СД2 увеличивалась с возрастом, у людей в воз-расте ≥70 лет такой тенденции не отмечено.…”
Section: Discussionunclassified
“…По данным исследования NATION, также наиболее высокая частота СД2 отмечалась у людей в возрасте 65-69 лет -13,6%. Как справедливо от-мечают авторы исследования NATION, полученные сведе-ния важны, так как в этой возрастной группе наблюдается высокая распространенность заболеваний сердечно-сосу-дистой системы, терапия которых становится более слож-ной при наличии сопутствующего СД [13][14][15][16].…”
Section: основные результаты исследованияunclassified
“…11,[14][15][16] It seems that non-HDL would be a better predictor than LDLc of unstable atherosclerotic plaque. 17 Reiner et al reported that 12.2% of coronary patients in whom the LDLc target value was reached had pathological levels of non-HDL-c. In our sample, only 7.33% patients had non-HDL-c levels > 110 mg/dL and LDL-c < 80 mg/dL after myocardial revascularization.…”
Section: Discussionmentioning
confidence: 99%